Effect of Inulin Concentration and Cooking Time on the Quality of Aloe Vera Jam - M.Rizki Firbiono Hardiadana; Lukman Hudi; Rahmah Utami Budiandari (jurnal makanan tropis dan teknologi agroindustri, 2022)
This study aims to determine effect of inulin concentration and cooking time on the quality of aloe vera jam. This study used factorial randomized block design. The first factor was concentration of inulin (I): (I1) 2%, (I2), 4% and (I3), 6%, the second factor was cooking time (L): (L1) 30 minutes (L2), 40 minutes and (L3) 50 minutes. Statistical analysis using analysis of variance and further test BNJ 5%. The results showed that there was significant interaction between inulin concentration and cooking time on the water content and lightness of aloe vera jam. Inulin concentration and cooking time had significant effect on the organoleptic characteristics of greasing power, texture and taste. Inulin concentration had significant effect on water content and lightness. Cooking time has significant effect on the vitamin C content, water content and lightness of aloe vera jam. The best treatment was aloe vera jam with I1L1 treatment (2% inulin concentration and 30 minutes of cooking time) with characteristics of vitamin C content 0.32%, water content 36.41%, lightness 44.97, redness 2.44 , yellowness 20.01 and the organoleptic of greasing power 3.03 (easy to spread-very easy to smear), texture 3.70 (smooth-very smooth), aroma 2.83 (slightly flavorful-fairly flavorful), and taste 3.40 (sweet-very sweet).